The answer is -1/3
The slope m is:
m = (y2 - y1) / (x2 - x1)
(x1, y1) = (-2, 2)
(x2, y2) = (4, 0)
m = (0 - 2) / (4 - (-2)) = -2 / 6 = -1/3
Question- The image is appearing blank for me, could you try and re-send it or forward it to me. Thank you.
Answer:
9+20t
Step-by-step explanation:
Look at the terms and see which has t and which is a number when you see like terms, add them or subtract them together to get like terms.
Answer:
![\frac{x}{4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B4%7D)
Step-by-step explanation:
The given function is
f(x) = 4x
As we know
f(x) = y, which implies x= ![f^{-1} (y)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%20%28y%29)
Therefore,
y = 4x
x = ![\frac{y}{4}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B4%7D)
as x= ![f^{-1} (y)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%20%28y%29)
So,
![f^{-1} (y) = \frac{y}{4}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%20%28y%29%20%3D%20%5Cfrac%7By%7D%7B4%7D)
replacing y by x in the above expression
![f^{-1} (x) = \frac{x}{4}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%20%28x%29%20%3D%20%5Cfrac%7Bx%7D%7B4%7D)
So our inverse function is ![\frac{x}{4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B4%7D)